2017
DOI: 10.1007/978-3-319-61425-0_5
|View full text |Cite
|
Sign up to set email alerts
|

ReaderBench Learns Dutch: Building a Comprehensive Automated Essay Scoring System for Dutch Language

Abstract: Abstract. Automated Essay Scoring has gained a wider applicability and usage with the integration of advanced Natural Language Processing techniques which enabled in-depth analyses of discourse in order capture the specificities of written texts. In this paper, we introduce a novel Automatic Essay Scoring method for Dutch language, built within the Readerbench framework, which encompasses a wide range of textual complexity indices, as well as an automated segmentation approach. Our method was evaluated on a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In this paper, we investigate how automated essay scoring methods can help to reduce the teachers´ work load. In a preliminary study the automated essay scoring method for the reports in the VIBOA game demonstrated a validity level of 75.1% in correctly predicting a pass or a failure (Dascalu, Westera, Ruseti, Trausan-Matu, & Kurvers, 2017). Although this rate is substantial, it is considered insufficient for practical application.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate how automated essay scoring methods can help to reduce the teachers´ work load. In a preliminary study the automated essay scoring method for the reports in the VIBOA game demonstrated a validity level of 75.1% in correctly predicting a pass or a failure (Dascalu, Westera, Ruseti, Trausan-Matu, & Kurvers, 2017). Although this rate is substantial, it is considered insufficient for practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Many AES methods have been developed over the past decades, and can generally be categorized as feature-engineering and neural-network approaches (Hussein et al, 2019;Ke and Ng, 2019). The featureengineering approach predicts scores using handcrafted features such as essay length or spelling errors (e.g., (Amorim et al, 2018;Dascalu et al, 2017;Mark D. Shermis, 2016;Nguyen and Litman, 2018)). The advantages of this approach include interpretability and explainability.…”
Section: Introductionmentioning
confidence: 99%
“…Several existing text analysis tools can calculate a huge number of textual features against input texts. ReaderBench [22] is an open source multilingual framework that makes use of natural language processing techniques to provide text analysis tools. The framework is multilingual [23] -text analysis tools are available in Dutch, French, Romanian and English.…”
Section: Introductionmentioning
confidence: 99%